Prognostic Value of Biomarkers in Cancer Patients Treated With Immune Checkpoint Inhibitor Therapy - Christopher Mann, MD; Ulrike Pailer, MSc; Andreas Spannbauer, MD; Fardin Hamidi, MD; Aliza Veronika Braser; Martin Hülsmann, MD; Christian Gerges, MD, PhD; Michael Gottsauner-Wolf, MD; Mariann Gyöngyösi, MD; Markus Raderer, MD; Martin Riesenhuber, MD, PhD; Christian Hengstenberg, MD; et al. (JACC: Advances)
Background: Immune checkpoint inhibitors (ICIs) have improved outcomes for several malignancies, but cancer patients face an increased risk of cardiovascular disease due to shared risk factors, similar biological mechanisms, and cardiotoxic side effects of therapy. Effective risk stratification strategies are urgently needed. Objectives: This study explored the association between the biomarkers with the risks of acute cardiovascular hospitalizations and death in cancer patients receiving ICI therapy. Methods: We used electronic health records of patients treated with ICI who had available baseline N-terminal pro-B-type natriuretic peptide (NT-proBNP) levels at Vienna General Hospital between January 2017 and July 2022. The primary outcome of interest was the composite of acute cardiovascular hospitalization heart failure or death. Cox regression models were adjusted for age, sex, estimated glomerular filtration rate, diabetes, coronary artery disease, heart failure, hypertension, atrial fibrillation, C-reactive protein, and low-density lipoprotein cholesterol. Results: Among 550 patients (35% female, age 65 years), median NT-proBNP levels were 272 pg/mL (Q1-Q3: 102-742), with 388 patients (71%) having levels ≥125 pg/mL. Over a median follow-up of 67 weeks, 190 patients (35%) died, and 103 cardiovascular hospitalizations (most commonly due to stroke, coronary artery disease, and heart failure) occurred in 76 patients (14%), resulting in a primary composite endpoint rate of 46.7 events per 100 patient-years. After multivariable adjustment, NT-proBNP remained independently associated with an increased risk of cardiovascular hospitalization and death (adjusted HR for 1-SD increase in log-transformed biomarker: 1.29; 95% CI: 1.06-1.33). Conclusions: These data highlight NT-proBNP levels as a valuable marker for identifying cancer patients at increased risk for cardiovascular events during ICI therapy.